Separation of BSA through FAU-type zeolite ceramic composite membrane formed on tubular ceramic support: Optimization of process parameters by hybrid response surface methodology and biobjective genetic algorithm. Issue 7 (9th August 2017) - Vinoth Kumar, R.; Ganesh Moorthy, I.; Pugazhenthi, G.
ABSTRACT: In this study, Faujasite (FAU) zeolite was coated on low-cost tubular ceramic support as a separating layer through hydrothermal route. The mixture of silicate and aluminate solutions was used to create a zeolitic separation layer on the support. The prepared zeolite ceramic composite membrane was characterized using X-ray powder diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), particle size distribution (PSD), field emission scanning electron microscopy (FESEM), and zeta potential measurements. The porosity of ceramic support (53%) was reduced by the deposition of FAU (43%) zeolite layer. The pore size and water permeability of the membrane were evaluated as 0.179 µm and 1.62 × 10 −7 m 3 /m 2 s kPa, respectively, which are lower than that of the support (pore size of 0.309 µm and water permeability of 5.93 × 10 −7 m 3 /m 2 s kPa). The permeate flux and rejection potential of the prepared membrane were evaluated by microfiltration of bovine serum albumin (BSA). To study the influences of three independent variables such as operating pressure (68.94–275.79 kPa), concentration of BSA (100–500 ppm), and solution pH (2–4) on permeate flux and percentage of rejection, the response surface methodology (RSM) was used. The predicted models for permeate flux and rejection were further subjected to biobjective genetic algorithm (GA). The hybrid RSM-GA approach resulted in a maximum permeate flux of 2.66 × 10 −5 m 3 /m 2 s and BSA rejection of 88.02%, at which the optimum conditions were attained as 100 ppm BSA concentration, 2 pH solution, and 275.79 kPa applied pressure. In addition, the separation efficiency was compared with other membranes applied for BSA separation to know the potential of the fabricated FAU zeolite ceramic composite membrane.